Методи управління трафіком із забезпеченням відмовостійкості та мережної безпеки на основі використання динамічних тензорних моделей телекомунікаційних систем - Єременко, О. С. (My University, 2018)
Дисертаційна робота присвячена вирішенню актуальної наукової проблеми, яка полягає в розвитку теорії управління трафіком з підтримкою якості обслуговування за множиною показників в умовах нестаціонарного режиму роботи телекомунікаційної мережі із забезпеченням її відмовостійкості та мережної безпеки. Вдосконалено та досліджено систему динамічних тензорних моделей QoS-маршрутизації та управління трафіком з формулюванням динамічних умов забезпечення якості обслуговування. Проведено розробку та дослідження моделей і методів відмовостійкої маршрутизації в телекомунікаційних мережах. Розроблено методи безпечної маршрутизації та швидкої перемаршрутизації за шляхами, що перетинаються. Проведено оцінку ефективності та розробку науково-методичних рекомендацій щодо практичного використання запропонованих у дисертації рішень в області забезпечення відмовостійкості та мережної безпеки при управлінні трафіком з підтримкою якості обслуговування в мультисервісних телекомунікаційних мережах. The dissertation is devoted to the solution of the relevant scientific problem, which consists in the development of the theory of traffic management with support of Quality of Service (QoS) for a set of parameters under the conditions of nonstationary mode of the telecommunication network (TCN) operation with ensuring its fault-tolerance and network security. The analysis conducted in the dissertation showed that the key technological tools for ensuring the QoS, fault-tolerance, and network security in modern TCN are protocol means of routing and traffic management in general, to the efficiency level of which the increasingly stringent requirements regarding the computational complexity and scalability of the obtained network solutions are put forward. The development and research of the system of dynamic tensor models of QoSrouting and traffic management and formulation of the conditions for ensuring the Quality of Service are carried out. The two-level method of intra-domain hierarchical coordination QoS-routing based on resource reservation with the support of end-toend Quality of Service on the parameters of the transmission rate and the average end-to-end packet delay through the use of the tensor TCN model has been further developed. The dynamic model of multipath routing with the provision of Quality of Service has been proposed for the parameter of the probability of timely delivery of packets in TCN for the first time.
Keywords: телекомунікаційна мережа; управління трафіком; маршрутизація; відмовостійкість; мережна безпека; пропускна здатність; міжкінцева затримка; якість обслуговування; telecommunication network; traffic management; routing; fault-tolerance; network security; bandwidth; end-to-end delay; balancing; Quality of Service